Cultivating a growth mindset within a blended learning environment at a University in South Africa: a design-based research study - Titus, Fahiema (School of Education, 2025)
This Design Based Research study attempts to unlock the spirit of personal empowerment among professional adult learners within the higher educational system through an interpretivist qualitative lens of observation and reflection. Adult Learners in this research include the educators assigned to transmit subject information and the professional development of relevant skills and competencies as required within a Blended Learning Environment. Candidates were selected from professional academic, training and learning institutions and the sample of individuals hold professional positions in their respective fields. The workshop practices were based on simplified hand, eye, body, breathing, calming, mental stimulations to enhance the awareness of their ability to self regulate their thinking, emotional and physiological processes. Furthermore, the outcomes of the research also showcase how often overlooked qualities of Human Excellence can be unhinged through Intentionality, Awareness and Attentional Training, Reflection/ Contemplation, and Mindful Learning Processes. The overall analysis and feedback sessions are drawn from the candidates' demonstrable understanding of their ability to enhance awareness of their personal perceptions, biases, internal energies, proprioception, mental states, and habitual behavioural conditioning. These components of personal change within a blended learning space are designed as part of the Foundational and Intermittent phases of application to the professional development program. Design principles and related artefacts derived from the DBR methodology provide educators and researchers a means by which educational practices are potentially optimised. In conclusion this DBR incentivises researchers, adult educators and policymakers to deepen investigations in improving professional development standards and practices within Blended Learning environments in the Higher learning institutions.